Structural and physiological neurovascular changes in idiopathic Parkinson’s disease and its clinical phenotypes - Al-Bachari, Sarah; Vidyasagar, Rishma; Emsley, Hedley CA; Parkes, Laura M (Journal of cerebral blood flow and metabolism, 2017)
Neurovascular changes are likely to interact importantly with the neurodegenerative process in idiopathic Parkinson’s disease (IPD). Markers of neurovascular status (NVS) include white matter lesion (WML) burden and arterial spin labelling (ASL) measurements of cerebral blood flow (CBF) and arterial arrival time (AAT). We investigated NVS in IPD, including an analysis of IPD clinical phenotypes, by comparison with two control groups, one with a history of clinical cerebrovascular disease (CVD) (control positive, CP) and one without CVD (control negative, CN). Fifty-one patients with IPD (mean age 69.0 ± 7.7 years) (21 tremor dominant (TD), 24 postural instability and gait disorder (PIGD) and six intermediates), 18 CP (mean age 70.1 ± 8.0 years) and 34 CN subjects (mean age 67.4 ± 7.6 years) completed a 3T MRI scan protocol including T2-weighted fluid-attenuated inversion recovery (FLAIR) and ASL. IPD patients showed diffuse regions of significantly prolonged AAT, small regions of lower CBF and greater WML burden by comparison with CN subjects. TD patients showed lower WML volume by comparison with PIGD patients. These imaging data thus show altered NVS in IPD, with some evidence for IPD phenotype-specific differences.